Flammability in tropical savannas: Variation among growth forms and seasons in Cerrado - Zanzarini, Vagner [UNESP]; Andersen, Alan N.; Fidelis, Alessandra [UNESP] (Wiley, 2022)
The herbaceous layer is the dominant fuel for fire in tropical savannas, the world's most fire-prone biome. However, little is known about variation in flammability among different growth forms, as well as how flammability varies seasonally. Here, we describe such variation in Brazilian Cerrado, the world's most phytodiverse tropical savanna. We measured three components of flammability (maximum burning temperature, burning rate, and burnt biomass) and morphophysiological traits (dead biomass percentage, moisture content, and specific leaf area) of five species of each of grasses, forbs, and shrubs throughout the wet and dry season. We found that grasses were the most flammable growth form and that their flammability was highest in the middle of the dry season when the percentage of dead biomass was highest (60%), and moisture content was low (25%). Flammability did not vary across seasons for either forbs or shrubs. Dead biomass, moisture content, and specific leaf area were all strongly correlated with flammability. These findings explain the dominant role played by grasses as drivers of flammability in tropical savannas, and they improve our understanding of how savanna flammability varies across space and time depending on the composition of the grass layer and its level of seasonal curing. This enables a better prediction of fire spread and behavior in different savanna types based on grass-layer composition.
Keywords: fire; leaf moisture content; neotropical savanna; plant flammability; plant growth forms; plant traits